2023
DOI: 10.1186/s12885-023-10566-2
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with the uptake of clinical breast examination among women of reproductive age in Lesotho: analysis of a national survey

Abstract: Background In low-resource settings with weak health systems, the WHO recommends clinical breast examination (CBE) as the most cost-effective breast screening modality for women. Evidence shows that biennial CBE leads to significant downstaging of breast cancer in all women. Breast cancer is the second most common cancer among women in Lesotho with a weaker healthcare system and a low breast cancer screening rate. This study investigated the prevalence and factors associated with the uptake of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Higher educational attainment has been known all over the world to be significantly related to women’s awareness of breast cancer [ 33 , 36 38 ]. In all these studies, it was shown that women’s educational status increased their awareness and the chance of using screening services [ 13 , 33 , 36 38 ]. Women of higher educational status can read and comprehend health-related information compared to the non-educated women.…”
Section: Discussionmentioning
confidence: 99%
“…Higher educational attainment has been known all over the world to be significantly related to women’s awareness of breast cancer [ 33 , 36 38 ]. In all these studies, it was shown that women’s educational status increased their awareness and the chance of using screening services [ 13 , 33 , 36 38 ]. Women of higher educational status can read and comprehend health-related information compared to the non-educated women.…”
Section: Discussionmentioning
confidence: 99%
“…Healthcare providers are often more accessible in urban areas in Indonesia and Pakistan. Women between the ages of 45 and 49 years, married women, women with a higher educational level, women who listened to the radio at least once a week, those who read newspapers or magazines, and women in the wealthiest group were all more likely to be aware of breast cancer, according to a recent Lesotho study [41]. These results also compare to the results of our study with women in rural areas being less likely than those in urban areas to be aware of breast cancer.…”
Section: Discussionmentioning
confidence: 99%